Improving Learning Strategies and Motivation Through Constructivism Approach in Speaking Performance - Dili Nilakandi; Agustinus Bambang Setiyadi; Muhammad Sukirlan (Universitas Islam Negeri Palopo, 2026)
This study investigated the improvement learning strategies, self-determined motivation, self- regulated learning (SRL), and speaking performance among Indonesian 11th grade students through a constructivism approach. Drawing on Constructivism, Self-Determination Theory (SDT), and SRL frameworks, the study investigated how motivation and learning strategies contribute to oral proficiency. Data were collected using a Learning Strategy Questionnaire, a Motivation Scale, and a Speaking Test, and analyzed through Paired Sample T-Tests, Product Moment Correlation and One Way Annova. Findings revealed a significant improvement in speaking performance, with mean scores rising from 16.40 to 17.83 (t = 8.509, p < 0.05). Motivation showed a weak, non- significant correlation with speaking in the pre-test (r = 0.360, p > 0.05) but a strong, significant correlation in the post-test (r = 0.675, p < 0.01). Strategy comparisons further indicated that metacognitive learners significantly outperformed cognitive and socio-affective groups, by nearly 10 and 8.5 points respectively. Strategy analysis further demonstrated that metacognitive learners significantly outperformed both cognitive and socio-affective groupsy nearly 10 and 8.5 points, respectively, highlighting the effectiveness of planning, monitoring, and evaluating in speaking development. These findings confirm that integrating motivational support with metacognitive strategy training is a powerful pedagogical approach for improving communicative competence.